Increased skin conductance responses and neural activity during fear conditioning are associated with a repressive coping style - Klucken, Tim; Kruse, Onno; Schweckendiek, Jan; Stark, Rudolf (Frontiers in Behavioral Neuroscience, 2015)
The investigation of individual differences in coping styles in response to fear conditioning is an important issue for a better understanding of the etiology and treatment of psychiatric disorders. It has been assumed that an avoidant (repressive) coping style is characterized by increased emotion regulation efforts in context of fearful stimuli as compared to a more vigilant coping style. However, no study so far has investigated the neural correlates of fear conditioning of repressors and sensitizers. In the present fMRI study, 76 participants were classified as repressors or as sensitizers and were exposed to a fear conditioning paradigm, in which the CS+ predicted electrical stimulation, while another neutral stimulus (CS-) did not. In addition, skin conductance responses (SCRs) were measured continuously. As the main findings, we found increased neural activations in repressors as compared to sensitizers in the ventromedial prefrontal cortex and the anterior cingulate cortex during fear conditioning. In addition, elevated activity to the CS+ in amygdala, insula, occipital, and orbitofrontal cortex as well as conditioned SCRs were found in repressors. The present results demonstrate increased neural activations in structures linked to emotion down-regulation mechanisms like the ventromedial prefrontal cortex, which may reflect the increased coping effort in repressors. At the same time, repressors showed increased activations in arousal and evaluation-associated structures like the amygdala, the occipital cortex, and the orbitofrontal cortex, which is also mirrored in increased SCRs. The present results support recent assumptions about a two-process model of repression postulating a fast vigilant response to fearful stimuli, but also a second emotion down-regulating process.